Family Altar as a Papuan Contextual Missiology Education in Christian Family Environment - Yohanes Kristian Labobar (International Journal of Asian Education, 2023)
This research aims to know and understand the position of the family altar in local Papuan culture in maintaining the holiness of today's increasingly modern families and realizing the mission of Christ. The research method used is Qualitative with an Ethnographic approach. The primary data sources in this study consist of individuals familiar with and engaging in Family Altar rituals. Meanwhile, secondary data sources encompass existing scientific literature. The researcher selected participants and respondents non-randomly, specifically opting for purposeful sampling. This approach involved the deliberate selection of participants and respondents, including ten families represented by functional church workers such as pastors, elders, and shamas, as well as five young individuals categorized as youths. Finally, the research results contribute to constructing this ritual tradition's values into the congregation's families who struggle with multi-ethnic, multi-cultural, and multi-religious challenges and still survive and mission elegantly.